Isolation of two novel Chlorella vulgaris and Tetraselmis chui mutants with improved protein contents and pigments for food applications - Bombo, Gabriel da Cunha (2022)
Microalgae are a worldwide food source, largely consumed by humans as food or, indirectly, as feed. Their biomass might contain high levels of protein, lipids, fatty acids, amino acids, and vitamins. They are unicellular organisms capable of living in the most diverse environments, being able to grow faster than other photoautotrophs and in non-conventional growth media that do not require either potable water or arable land. With such characteristics, microalgae can become an important alternative food source in the near future since the world population is estimated to reach 10 billion people before 2050. Microalgae are produced and consumed as high-quality nutritional food, but there is an urgent need to improve existing microalgae-based products since their organoleptic properties, such as their “grassy” taste, are not consensually accepted by the consumer. The present work aims to create new strains from microalgal species already registered as novel food, namely Chlorella vulgaris and Tetraselmis chui, to improve the quality of the produced biomass and the overall consumer acceptance. For this purpose, random chemical mutagenesis using the alkylating agent ethyl methane sulphonate (EMS) was carried out to generate mutants with higher protein contents and/or lower amounts of chlorophyll. Afterwards, the best performing strains were selected using visual scoring regarding pigmentation and flow cytometry techniques. Upon implementing this selection pipeline, two C. vulgaris strains were isolated, namely the C3 strain, a non-mutagenized isolate able to grow significantly faster on solid medium compared to the wildtype (WT) culture; and a second mutant, GL3, obtained from the C3 strain. Although the C3 strain presented higher protein contents, the GL3 displayed vestigial chlorophyll contents, lower carotenoid levels, and higher protein content than the original WT strain. The GL3 strain grown under heterotrophic conditions reached higher cell concentrations as compared to the WT, strongly suggesting that the mutant strain GL3 might become a relevant source of protein, being suitable to be produced on a larger scale to generate food products with enhanced organoleptic properties.